Experimental and numerical analysis of fracture parameters of adhesively bonded joints at low temperatures. (15th February 2019) - Rahmani, A.; Choupani, N.
Highlights: Tensile properties of the adhesive joints were obtained at low temperatures. FE analysis was carried out at low temperatures and various loading modes. Mixed mode fracture tests were conducted by using the special loading device. Fracture surfaces of samples were analyzed by SEM. Abstract: In this work, the fracture parameters of the adhesive joints were investigated at low temperatures. The results of the tensile experiments showed that by decreasing the temperature, the ultimate strength, yield strength and elastic modulus have increasing trends. The effect of temperature and loading mode on the fracture toughness parameters of adhesive joints were examined by using the special test loading device in which by varying the loading angle, pure mode I, II and mixed mode data were obtained experimentally. The results showed that by decreasing the temperature, critical stress intensity factors and critical strain energy release rates increased. However, the increasing trend in mode I was gentle and in mode II was significant. Non-dimensional stress intensity factors were also determined by using finite element method at low temperatures and different loading modes. In order to understand the failure mechanism of adhesive joints, fracture surfaces of samples were analyzed, which showed that, in mode I, the failure mechanism was of a cohesive type and by decreasing the temperature, the joint became brittle and the fracture surface became smooth. The interfacial failure in mode II revealed that the fracture toughness of the adhesive was greater than that of the interface, which leads to deviation of crack growth path from the cohesive to the interfacial fracture.